Kedudukan Hukum Hak Pengelolaan Tanah Ulayat yang Dijadikan Jaminan Pihak Ketiga dalam Kerjasama - Firmansyah; Yunaldi, Wendra (Universitas Medan Area, 2024)
This research aims to determine the basic provision of land management rights in Minister of Agrarian Regulation number 18 of 2021, the basic provision of land management rights in Minister of Agrarian Regulation Number 18 of 2021 and to determine the position of management rights which are used as collateral after the implementation of Government Regulation Number 18 of 2021 Regarding Management Rights. To find out the consequences of management rights which are used as collateral based on Minister of Agrarian Regulation number 18 of 2021. This research uses a type of normative research with statutory, case and conceptual approaches which are analyzed descriptively qualitatively. The results of this research are that there are overlapping regulations relating to land management rights which are used as collateral. The conclusion of this research is that after the enactment of Minister of Agrarian Regulation Number 8 of 2021, there is the potential to cause conflict related to collateral because there is an overlap between government regulations and ministerial regulations. number 8 of 2021